Trade reform and regional dynamics: Evidence from 25 years of Brazilian matched employer-employee data - Rafael Dix-Carneiro; Brian K. Kovak (W.E. Upjohn Institute for Employment Research, 2015)
We empirically study the dynamics of labor market adjustment following the Brazilian trade reform of the 1990s. We use variation in industry-specific tariff cuts interacted with initial regional industry mix to measure trade-induced local labor demand shocks, and then examine regional and individual labor market responses to those one-time shocks over two decades. Contrary to conventional wisdom, we do not find that the impact of local shocks is dissipated over time through wage-equalizing migration. Instead, we find steadily growing effects of local shocks on regional formal sector wages and employment for 20 years. This finding can be rationalized in a simple equilibrium model with two complementary factors of production, labor and industry-specific factors such as capital, that adjust slowly and imperfectly to shocks. Next, we document rich margins of adjustment induced by the trade reform at the regional and individual level. Workers initially employed in harder hit regions face continuously deteriorating formal labor market outcomes relative to workers employed in less affected regions, and this gap persists even 20 years after the beginning of trade liberalization. Negative local trade shocks induce workers to shift out of the formal tradable sector and into the formal nontradable sector. Non-employment strongly increases in harder-hit regions in the medium run, but in the longer run, non-employed workers eventually find re-employment in the informal sector. Working age population does not react to these local shocks, but formal sector net migration does, consistent with the relative decline of the formal sector and growth of the informal sector in adversely affected regions.
Keywords: F14; F16; J6; J46; 330; Local labor markets; Trade liberalization; Transitional dynamics